Systematic RPG Development Maximizes Player Engagement in Global Context: Pengembangan RPG yang Sistematis Memaksimalkan Keterlibatan Pemain dalam Konteks Global - Hidayatullah, Vika Tanjung; Astutik, Ika Ratna Indra; Ariyanti, Novia; Busono, Suhendro (Indonesian Journal of Innovation Studies, 2024)
This study presents the systematic development of an Adventure RPG game titled "Tomorrow Will Come" using the ADDIE method, aiming to enhance understanding of RPG game development. Leveraging the Godot Engine and GDscript programming language, the research follows the Analysis, Design, Development, Implementation, and Evaluation phases. Feedback from beta testers highlights positive gameplay experiences but suggests room for improvement, particularly in gameplay difficulty. The findings underscore the significance of iterative design and player feedback in refining game mechanics. Overall, this research contributes to advancing RPG game development methodologies and emphasizes the importance of innovation and user-centric design in creating compelling gaming experiences. Highlight: 1. ADDIE method enhances structured RPG game development. 2. Player feedback refines mechanics, enhancing overall quality. 3. Godot Engine innovates technical aspects, prioritizing user-centric design. Keyword: RPG game development, ADDIE method, Godot Engine, Player feedback, Iterative design